113k views
3 votes
Last question I need help with. (40 points)

Last question I need help with. (40 points)-example-1
User MikeD
by
5.0k points

2 Answers

0 votes

Answer:

hello :


(f-g)(x) = x^(4) - x^(3) - 4x^(2) - 3

Explanation:


(f - g)(x) = f(x) - g(x) = (x^(4) -x^(2) +9) - (x^(3) +3x^(2) +12) &nbsp; &nbsp; &nbsp; &nbsp; &nbsp; &nbsp; = x^(4) -x^(2) +9 - x^(3) - 3x^(2) - 12</p><p>(f - g)(x) = x^(4) - x^(3) - 4x^(2) -3

User Georgi Stoyanov
by
5.1k points
1 vote

Answer:

x^4 -x^3 -4x^2 -3

Explanation:

f(x) = x^4 -x^2 +9

g(x) = x^3 +3x^2 +12

We are subtracting

f(x) -g(x) =x^4 -x^2 +9 - ( x^3 +3x^2 +12)

Distribute the minus sign

x^4 -x^2 +9 - x^3 -3x^2 -12

I like to line them up vertically

x^4 -x^2 +9

- x^3 -3x^2 -12

-------------------------

x^4 -x^3 -4x^2 -3



User Felipe Ardila
by
6.5k points